Decontamination effect of neutral electrolysed water for spray nozzles of electric warm-water bidet toilet seats in the healthcare setting. Issue 2 (June 2021) - Itami, Aiko; Hori, Satoshi; Misawa, Shigeki
Summary: Background: There has been an increasing demand for more sanitary bidet seats in many healthcare settings because of concerns regarding potential contamination of the spray nozzles of warm-water bidet toilet seats. This contamination is thought to possibly serve as a reservoir for horizontal transmission of drug-resistant bacteria. Aim: This study was performed to determine the optimal Pseudomonas aeruginosa decontamination conditions and verify the effectiveness of these decontamination conditions. Methods: An in vitro test of rinsing with neutral electrolysed water was performed using seven strains of P. aeruginosa. The decontamination effect of the neutral electrolysed water was verified by a field test involving an analysis of the number of bacteria isolated from samples collected from the spray nozzles and the sprayed water from 10 toilet seats at the internal medicine ward of Juntendo University Hospital. Findings: The in vitro test results showed that the decontamination effect of neutral electrolysed water tended to be higher with higher free chlorine concentrations in the nozzle-cleaning water and shorter intervals of rinsing. The field test involving the hospital ward toilets showed that routine physical cleaning was satisfactorily effective. Conclusion: The study results suggest that the risk of horizontal transmission of drug-resistant bacteria via the use of bidet toilet seats in hospitals can be reduced by general cleaning and appropriate control of the free chlorine concentration in the nozzle-cleaning water.